Magnetic flux generation and transport in cool stars - Işık, Emre; Schmitt, D.; Schuessler, M. (Edp Sciences S A, 17, Ave Du Hoggar, Pa Courtaboeuf, Bp 112, F-91944 Les Ulis Cedex A, France, 2011)
Context. The Sun and other cool stars harbouring outer convection zones manifest magnetic activity in their atmospheres. The connection between this activity and the properties of a deep-seated dynamo generating the magnetic flux is not well understood. Aims. By employing physical models, we study the spatial and temporal characteristics of the observable surface field for various stellar parameters. Methods. We combine models for magnetic flux generation, buoyancy instability, and transport, which encompass the entire convection zone. The model components are: (i) a thin-layer alpha Omega dynamo at the base of the convection zone; (ii) buoyancy instabilities and the rise of flux tubes through the convection zone in 3D, which provides a physically consistent determination of emergence latitudes and tilt angles; and (iii) horizontal flux transport at the surface. Results. For solar-type stars and rotation periods longer than about 10 days, the latitudinal dynamo waves generated by the deep-seated alpha Omega dynamo are faithfully reflected by the surface distribution of magnetic flux. For rotation periods of the order of two days, however, Coriolis acceleration of rising flux loops leads to surface flux emergence at much higher latitudes than the dynamo waves at the bottom of the convection zone reach. A similar result is found for a K0V star with a rotation period of two days. In the case of a rapidly rotating K1 subgiant, overlapping dynamo waves lead to noisy activity cycles and mixed-polarity fields at high latitudes. Conclusions. The combined model reproduces the basic observed features of the solar cycle. The differences between the latitude distributions of the magnetic field at the bottom of the convection zone and the emerging surface flux grow with increasing rotation rate and convection zone depth, becoming quite substantial for rapidly rotating dwarfs and subgiants. The dynamical evolution of buoyantly rising magnetic flux should be considered as an essential ingredient in stellar dynamo models.
Keywords: Sun: activity; Sun: dynamo; Stars: interiors; Stars: late-type; Stars: activity; Stars: magnetic field; Solar Convection Zone; Differential Rotation; Activity Cycles; Main-Sequence; Polar Spots; Tubes; Dynamo; Surface; Güneş: etkinlik; Güneş: dinamo; Yıldız: iç; Yıldız: Geç tip; Yıldız: etkinlik; Yıldız: manyetik alan; Güneş Konveksiyon Bölgesi; Diferansiyel Rotasyon; Etkinlik Çevrimleri; Anakol; Kutup Noktalar; Tüpler; Dinamo; Yüzey